In situ SiN/AlN/GaN HEMTs with regrown contacts using selective etching - Can Cao; Sheikh Ifatur Rahman; Chris Chae; Jinwoo Hwang; Chandan Joishi; Siddharth Rajan; Wu Lu (Applied Physics Express, 2025)
We show AlN/GaN high electron mobility transistors with in situ SiN for passivation and regrown n ^+ GaN ohmic contacts using a selective etching process that is more suitable for device scaling. The regrown ohmic contacts have a clean and sharp edge definition with a contact resistance of 0.25 Ω·mm. The interfacial resistance between the regrown n ^+ GaN and the 2DEG at AlN/GaN interface is 0.058 Ω·mm, close to the theoretical quantum conductance limit. The fabricated devices with a gate length of 0.7 μm exhibit a maximum current density of 1.57 A mm ^−1 and on-resistance of 1.85 Ω·mm at a gate bias of 1 V.